The discovery and conquest of Peru : chronicles of the New World encounter - Cieza de León, Pedro de, 1518-1554 (Latin America in translation/en traducción/em tradução., 1998)
Initial translation into English of a first-person account of the 16th century conquest of Peru, written by a Spanish soldier and naturalist; Pedro de Cieza de Leon was one of the first Europeans in the Andean region of South America to use native inform.